ANALYSIS OF HUMAN–ELEPHANT CONFLICT AND ITS ECONOMIC IMPACTS USING A COMMUNITY-BASED APPROACH IN THE PEUSANGAN WATERSHED, ACEH - Muhardi; Ernawita; Syifa Saputra (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Human–elephant conflict has become an increasingly significant environmental issue in Indonesia, particularly in the Peusangan Watershed, Aceh, affecting ecological, social, and economic aspects of local communities. This study aims to identify the main factors causing human–elephant conflict, analyze its economic impacts, and examine community-based mitigation efforts implemented at the local level. The research employed a descriptive exploratory approach using an ex-post facto method through interviews and field observations involving communities in Pantan Lah, Blang Rakal, and Karang Ampar villages. The results indicate that the conflict is primarily driven by habitat loss and fragmentation, microclimate changes, resource competition, and negative community perceptions toward elephants. The highest number of conflict cases was recorded in Karang Ampar Village (53 cases), followed by Blang Rakal (14 cases) and Pantan Lah (9 cases). The economic losses resulting from damage to agricultural and plantation land were estimated at IDR 2,733,800,000, leading to decreased productivity and community welfare. Community-based mitigation efforts include patrol activities, elephant deterrence measures, and participatory mapping of elephant movement corridors. These findings highlight that a community-based approach plays a crucial role in supporting sustainable conflict mitigation.